SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPPLIER DENGAN METODE ANALYTICAL HIERARCHY PROCESS PADA PT. CIPTA NUANSA PRIMA TANGERANG - Rani Irma Handayani; Yuni Darmianti (Jurnal Techno Nusa Mandiri, 2017)
The supplier is one of the most important parts of a construction service company. To get the best result, it needs the best and quality supplier. One effort to get those suppliers is to perform supplier selection, therefore supplier selection is necessary for a construction service company. Since many suppliers, PT. Cipta Nuansa Prima Tangerang had trouble in choosing a supplier with their respective advantages. The process of supplier selection uses the AHP (Analytical Hierarchy Process) method, which outlines the criteria into the process of comparing alternatives. The greater the value generated, then the main well for those suppliers will be chosen. The criteria of supplier selection on PT. Cipta Nuansa Prima Tangerang is delivery, service, product, quality, and price. The supplier selection uses the AHP method with tools Expert Choice and proven with Ms. Excel allow the company to support the decision. AHP method is the best solution to be a Decision Support System for solving the problem and contribute management for making decision more objective of supplier selection.